Oral Presentations Abstracts: SELF-TRACKING AS A THREAT TO SOLIDARY HEALTHCARE? A POWER-CRITICAL APPROACH TOWARDS SOLIDARITY IN DIGITALIZED HEALTH CARE - ELLERICH-GROPPE, Niklas (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Smart technologies enable an increasing personalization of health care services. This becomes salient in the phenomenon of self-tracking: Health- and fitness-tracking devices are used to control and optimize individual health behavior and to facilitate individually tailored medical prevention and care. While the insurance industry takes an interest in self-tracking data and promises better tariffs and bonus points for those with a healthy lifestyle, consumer protectors warn against personalized risks, discrimination and eroding solidarity. However, the concept of solidarity involved in these debates is often still less than clear, especially with regard to its normative implications and associated power-relations. Against this backdrop, I propose and discuss a power-critical perspective on solidarity in digitalized health care. In an exploratory approach, I first map the relevant power-relations in conjunction with self-tracking data in the insurance industry. As I will argue, these power-relations need critical reflection as they challenge common understandings of solidarity and thus the normative foundations of the welfare state. To this purpose, I provide an outline of a power-critical approach towards solidarity focusing especially on aspects of reciprocity and shared values as fundamental components of solidarity that are closely linked to power relations. Such an approach can help to re-conceptualize solidarity in the context of digitalized health care and thus provide a basis for critical analyses in smart bioethics.